Tourism in the city of São Paulo by bicycle: determinant factors in the choice of urban bicycle touring route - Souza, Cristina Sales Ferreira de; Souza, Raul Jose de (Brazilian Journal of Production Engineering, 2022)
This study analyzes the conditions that influence the tourist to use the bicycle as a means of transport when visiting an urban tourist destination. In this context, it is intended to find out what kind of motivations are perceived by cyclists during their travels for tourism purposes in the city of São Paulo. The methods comprise bibliographic and documentary research and empirical research. There was a significant number of individuals using the bicycle when visiting different parts of the city, privileging the pleasure of cycling and at the same time discovering its attractions. In this context, it was found that the bicycle represents a component that plays an important role not only as a means of transport, but also as a motivating element for visitors to explore the destination, learn about their culture, in addition to enjoying it with greater freedom of its attractions. Highlight, however, for the need for an urban bicycle infrastructure that allows visitors to fully enjoy the city's tourist potential.
Keywords: Bicycle tourism; Tourist; Tourist itinerary; Urban mobility; São Paulo